2010
DOI: 10.1021/jm9014179
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Structure, and Functional Elucidation of a Modified Pentapeptide, Cysteine Protease Inhibitor (CPI-2081) from Streptomyces Species 2081 that Exhibit Inhibitory Effect on Cancer Cell Migration

Abstract: Cysteine proteases play an important role in cell migration and tumor metastasis. Therefore, their inhibitors are of colossal interest, having potential to be developed as effective antimetastatic drugs for tumor chemotherapy. Traditionally, secondary metabolites from streptomyces show a wide range of diversity with respect to their biological activity and chemical nature. In this article, we have described the characterization of small molecule cysteine protease inhibitor, CPI-2081 (compound 1), a mixture of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In fact, the biological information of a protein sequence appears to reside in short aa strings. (31) A minimotif of only five residues can determine or inhibit essential cellular functions and processes such as cell adhesion and nerve regeneration, (32,33) apoptosis, (34) cancer cell proliferation (35) or migration, (36) thrombin activity, (37) and angiogenesis. (38) Moreover, it is well known that a pentapeptide represents a minimal recognition unit at the basis of the immune response, (39,40) and has an immunotherapeutic potential.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the biological information of a protein sequence appears to reside in short aa strings. (31) A minimotif of only five residues can determine or inhibit essential cellular functions and processes such as cell adhesion and nerve regeneration, (32,33) apoptosis, (34) cancer cell proliferation (35) or migration, (36) thrombin activity, (37) and angiogenesis. (38) Moreover, it is well known that a pentapeptide represents a minimal recognition unit at the basis of the immune response, (39,40) and has an immunotherapeutic potential.…”
Section: Resultsmentioning
confidence: 99%
“…39), isolated from a biologically active culture supernatant of Streptomyces sp. NCIM2081 by Sihgh et al in 2010, as the cysteine protease inhibitor, it is found that nanomolar concentration of compounds CPI-2081a is able to inhibit papain hydrolytic activity, it also showed significantly inhibitory activity of tumor cell migration at sub cytotoxic concentration [118,119].…”
Section: Indole-based Natural Products and Their Antiviral Activitymentioning
confidence: 99%
“…A mixture of two peptide metabolites from Streptomyces NCIM 2081 (Fig. 4) exhibited potent inhibitory action against papain and significantly inhibited tumor cell migration at subcytotoxic concentrations, indicating its remarkable potential to be developed as antimetastatic drug (Singh et al, 2010). …”
Section: Inhibitors From Natural Sourcesmentioning
confidence: 99%